Analysis of the quality of the scientific output concerning customer/ patient satisfaction - Teixeira Santos, Jéssica Adrielle; Inoue, Kelly Cristina; Seleghim, Maycon Rogério; Matsuda, Laura Misue (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To determine if Brazilian publications about patient satisfaction available online meet Hoppen et al. scientific quality criteria. Methodology. Descriptive-exploratory study. Literature search was made in the electronic databases MEDLINE and LILACS, using the descriptor “patient satisfaction”. After the first review of the results and refinement of the search, 14 full papers were selected and were used as the study sample. Results. Publications were diverse in its structural composition and did not adhere completely to the criteria established in the theoretical framework of this study. The less frequent items in the papers were: Theoretical reference (14.3%), research question (35.7%), assumptions (42.8%) and limits (14.3%). The updated references (92.8%), justification and objectives were present in 100% of the studies. Conclusion. Brazilian scientific publications about user satisfaction are structurally well articulated, however it is necessary a greater detailing of the methodology and the insertion of some requirements considered optional so the published content is not questioned or discredit.